Practices and challenges on coordinating the Brazilian Unified Health System - Luzia Beatriz Rodrigues Bastos; Maria Alves Barbosa; Claci Fátima Weirich Rosso; Lizete Malagoni de Almeida Cavalcante Oliveira; Ilma Pastana Ferreira; Diniz Antonio de Sena Bastos; Ana Cláudia Jaime de Paiva; Alex de Assis Santos dos Santos
ABSTRACT OBJECTIVE To analyze the obstacles and challenges faced by managers and coordination professionals in their practices in municipal coordinating centers. METHODS An exploratory descriptive study with a qualitative focus, applied in 40 managers and coordination professionals, from September 2017 to November 2018, with semi-structured interviews, resulting in two categories of analysis: limiting factors and factors that facilitate the management and operationalization of the Brazilian Unified Health System (SUS) coordinating sector. RESULTS Analyzing the statements, we found evidence of the following limiting factors: failure in the criteria of referral, unavailability of beds, high demand, systemic difficulties in relation to the coordinating system, procedures of difficult scheduling and execution, increased repressed demand for elective procedures and difficulties in the flow of information between primary care and coordination. In the category of facilitating factors, the most significant possibilities were: expansion of the capability to know the user's reality, improvement in primary care and increase in health financial resources, health training and education and restructuring, in addition to reorganizing internal coordinating procedures. CONCLUSION The limiting factors of coordination show the need to promote actions that offer all SUS users full access to health services.